BACK TO SCHOOL: STUDENTS’ WILLINGNESS TO ATTEND FACE-TO-FACE CLASSES IN THE NEW NORMAL EDUCATION SYSTEM - Reynaldo G. Barata, Ed.D. (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
This research sought to find the level of students' willingness to attend face-to-face classes in the new normal education system. The respondents of this study were 1,551 students of BPSU during the academic year 2021-2022. This study is quantitative research; thus, it uses a descriptive method of research design and fact-finding inquiry to assess and explain the relationship between the respondents' profiles and their willingness to attend face-to-face classes. Since this study was conducted during the pandemic, the researcher used Google Forms to gather data. The results of this study showed that students are much more willing to attend face-to-face classes in the new normal education system. There is a significant relationship between respondents' profiles in terms of COVID-19 vaccination, health comorbidities, experience in online classes, self-test anxiety, and their willingness to attend face-to-face classes in the new normal education system. Academic leaders would do well to understand student decisions, and their humanistic learnings must be judged concerning students' possession of the interests and beliefs that the respective academics in new normal environments seek to reinforce and reward at the time students enter face-to-face classes in the new normal education system.